2016
DOI: 10.2135/cropsci2016.04.0285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Key Methodology for Digital Image Analysis of Turfgrass Color Using Open‐Source Software

Abstract: Digital image analysis is a frequently used research technique to provide an objective measure of turfgrass color, in addition to the traditional visual rating. A commonly used method relies on commercial software package SigmaScan Pro to quantify mean hue angle, saturation, and brightness values from turf images, and to calculate a dark green color index as the measure of color. To enable turf image analysis to function on an open‐source platform, a method was developed within ImageJ to batch process turf ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Thus, experiments with digital image analysis are efficient to estimate the nutritional status of the lawn (Zhang et al, 2017), especially with regard to nitrogen, and corroborate the studies that correlate this analysis with nitrogen doses by Backes et al (2010), Lima et al (2012), Agati et al (2015) and Gazola et al (2016).…”
Section: Resultssupporting
confidence: 73%
“…Thus, experiments with digital image analysis are efficient to estimate the nutritional status of the lawn (Zhang et al, 2017), especially with regard to nitrogen, and corroborate the studies that correlate this analysis with nitrogen doses by Backes et al (2010), Lima et al (2012), Agati et al (2015) and Gazola et al (2016).…”
Section: Resultssupporting
confidence: 73%
“…Zhang et al. (2017) reported that θ generally outperformed saturation or brightness when used to identify turfgrass color variations among genotypes or due to fertility levels. However, the current research suggests concurrent analysis of saturation and brightness (or analogous components) along with θ may be required to obtain a more complete picture of color.…”
Section: Resultsmentioning
confidence: 99%
“…The same is true for DGCI. While DGCI was effective in assessing turf colors (Zhang et al., 2017) and does include aspects of saturation and brightness, it may not be suitable for examining colors other than green, which may preclude follow‐up assessment of shoots treated with herbicides or growth regulators or other chemicals or cultural practices known to elicit phytotoxicity reducing green color.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations